Turning straw into gold: specialization among damar agroforest farmers in pesisir, Sumatra - Wollenberg, Eva Karoline; Nawir, A.A. (2005)
As most nontimber forest products (NTFPs) are low cash value, their potential for generating significant income appears limited. Low value products can, however, result in significant incomes when people specialize in them.